2017
DOI: 10.1088/1361-648x/aa89c4
|View full text |Cite
|
Sign up to set email alerts
|

Sonogashira cross-coupling over Au(1 1 1): from UHV to ambient pressure

Abstract: We have studied the reaction of phenylacetylene (PA) with chloro-, bromo-, and iodobenzene on the Au(1 1 1) surface as a model system for the gold-catalysed Sonogashira cross-coupling. Both ultrahigh vacuum-based and ambient pressure x-ray photoelectron spectroscopy show that iodo- and chlorobenzene (IB and CB) undergo the cross-coupling reaction towards diphenylacetylene. Bromobenzene (BB), in contrast, does not react in the UHV experiments. Further, at ambient pressure signs are found for poisoning of the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Te mperature-programmed reaction (TPR) studies suggested that the temperature at whichS onogashira coupling occurs coincides with the temperature at which CÀIb ond scission of iodobenzene occurs over the Au(111)s urface (Scheme 75). [382] However,b romobenzene did not undergo the crosscoupling reaction. [376,380] Unlike the Au(111)s urface, the clean, smoothed Au(1 00)s urface showed lower reactivity toward CÀCc oupling than the roughened surface.…”
Section: Cross-coupling Reactions Activatedbyb Ulk Au Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Te mperature-programmed reaction (TPR) studies suggested that the temperature at whichS onogashira coupling occurs coincides with the temperature at which CÀIb ond scission of iodobenzene occurs over the Au(111)s urface (Scheme 75). [382] However,b romobenzene did not undergo the crosscoupling reaction. [376,380] Unlike the Au(111)s urface, the clean, smoothed Au(1 00)s urface showed lower reactivity toward CÀCc oupling than the roughened surface.…”
Section: Cross-coupling Reactions Activatedbyb Ulk Au Surfacesmentioning
confidence: 99%
“…[381] Av ery recent experimental study Schnadt et al found that both chlorobenzenea nd iodobenzene underwent Sonogashira coupling with phenylacetyleneo ver Au(111)s urfaces. [382] However,b romobenzene did not undergo the crosscoupling reaction.…”
Section: Cross-coupling Reactions Activatedbyb Ulk Au Surfacesmentioning
confidence: 99%
“…As an example, a recent study of the Sonogashira cross-coupling reaction (a C-C bond-formation reaction between iodo-or chlorobenzene and phenylacetylene to form diphenylacetylene) conrmed earlier UHV results that Au (111) catalyses the reaction at moderate temperature and pressure. 34 However, rapid inactivation due to the formation of a carbonaceous species was observed at higher temperature and pressure, 34 illustrating the importance of NAP-XPS in providing more industrially relevant conditions. Although, as we discuss in Section 2.7, it has recently become possible to carry out NAP-XPS at pressures of 1 bar and above of a few mbar, and there remain signicant challenges to solve in studying real catalytic reactions of large molecules.…”
Section: Applications In Heterogeneous Catalysismentioning
confidence: 99%